(untitled) (Fiep Bulletin - online, 2014)
This research was carried through from interviews with proprietors or managers of the Fitness Companies and had as objectives: to verify the level of financial investment of the Fitness Companies of Rio de Janeiro in programs of professional qualification; to investigate the predominant focus of the programs of professional training in Fitness Companies in Rio de Janeiro; to compare the level of investment and the predominant focus of the professional training with the demands of the market in this segment; and to study the coherence in the rising of the level of investment with focus in the professional training. It is concluded with regard to the level of investment of the companies that the training of the professors presents a higher distribution than the one of the coordinators, what by itself is a distortion. An imperfection is evidenced since the training of the professors presents a better distribution of its focus in the diverse abilities when compared with the training of the coordinators. The comparisons allow to conclude that the companies had presented a level of investment in professional training with regularity, in special for training of professors, either in the companies where they judged the professionals qualified in this area satisfactory or in the ones where they did not find satisfactory. It was observed that the continuous training of the professionals in the area of fitness is a concern of the companies, what is translated by investments in the qualification of the professionals, and propitiates the rising of the level of satisfaction of customers and employees.